PENGARUH PEMBERIAN KATA-KATA YANG MENGANDUNG EMOSI TERHADAP MEMORI KERJA: VISUOSPATIAL SKETCHPAD - Azkia, Jihan Faridatul; Yusuf, Larasati Maulana; Zulfa, Nazma Nayla; Maharani, Pradnya Pramitha; Ramadhina, Fenisa Candra (Yayasan Amanah Nur Aman, 2025)
Memory is important in a person's life to do every task given, as well as in daily life. Memory can be formed due to stimulus that is present in everyday life. Stimulus can be in the form of touch, movement, smell and sound. Not all stimuli are entered and processed by our brain and become a memory. One form of memory is visuospatial sketchpad which functions to process memory in visual and spatial form. Individuals will more easily remember a word if it contains certain emotions. In this study, the researcher's goal is to test whether there is an effect of giving words that contain emotions on visuospatial sketchpad. This research is experimental research, involving 14 students who are divided into three groups, namely groups with neutral, negative and neutral emotion words. The measuring instrument used in this study is CEFI. The analysis of this study used ANOVA test. The results showed that there were differences between groups with positive, negative and neutral emotion words (p = 0.013, F (2,11) = 6.687). This shows that. Based on the Post Hoc test, it was found that words containing negative emotions were easier to remember compared to words containing positive emotions.